2013
DOI: 10.1186/1471-2369-14-212
|View full text |Cite
|
Sign up to set email alerts
|

The association of very-low-density lipoprotein with ankle-brachial index in peritoneal dialysis patients with controlled serum low-density lipoprotein cholesterol level

Abstract: BackgroundPeripheral artery disease (PAD) represents atherosclerotic disease and is a risk factor for death in peritoneal dialysis (PD) patients, who tend to show an atherogenic lipid profile. In this study, we investigated the relationship between lipid profile and ankle-brachial index (ABI) as an index of atherosclerosis in PD patients with controlled serum low-density lipoprotein (LDL) cholesterol level.MethodsThirty-five PD patients, whose serum LDL cholesterol level was controlled at less than 120mg/dl, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…The results indicated in table (3) a significant increase in the level of ( p<0.001) in the levels of (LDL) in total serum patients compared to healthy, and that these results are consistent with the results of previous research indicated the high level (LDL) in serum blood of cancer patients and both genders and for all age groups [28] .In this case, the reason may be due to the decrease of (HDL) and the increase in the level of LDL and the oxidation rate is due to the increase in the quantities of free radicals, and that leads to decrease the levels of HDL and increased levels of LDL [29] .…”
Section: -Level Of Low-density Lipoproteins In Blood Vessels With Leukemiasupporting
confidence: 92%
See 1 more Smart Citation
“…The results indicated in table (3) a significant increase in the level of ( p<0.001) in the levels of (LDL) in total serum patients compared to healthy, and that these results are consistent with the results of previous research indicated the high level (LDL) in serum blood of cancer patients and both genders and for all age groups [28] .In this case, the reason may be due to the decrease of (HDL) and the increase in the level of LDL and the oxidation rate is due to the increase in the quantities of free radicals, and that leads to decrease the levels of HDL and increased levels of LDL [29] .…”
Section: -Level Of Low-density Lipoproteins In Blood Vessels With Leukemiasupporting
confidence: 92%
“…The reason for the high low-density lipoprotein On a large amount of triglycerides, which is formed in the liver by the liver cells cortical, which works to transfer (TG) and cholesterol to the rest of the body [29] . and the process of oxidation in the body contribute to the high level of (VLDL), which leads to a reduction in the level of effectiveness of the enzyme Lipoprotein lipase located in the tissues of the body and this decrease leads to malfunction In the level of fat and a rise in the level of triglyceride in the serum where the ratio of glycerides in (VLDL) is increasing, therefore, can be explained by the rise of (TG) in (VLDL) mechanism of the same height(TG) [30] .…”
Section: -The Level Of Very-low-density Lipoproteins In Blood Vessels With Leukemiamentioning
confidence: 99%
“…Laakso et al also reported that higher VLDL-C levels are associated with an increased risk of CVD in diabetic patients [29]. In dialysis, Kanda et al reported that VLDL-C is associated with peripheral artery disease (diagnosed using the ankle-brachial index) in PD patients with controlled LDL-C levels [20]. In the present study, similar results were observed; we found that elevated VLDL-C levels were associated with increased risks of all-cause and CV mortalities in patients treated with peritoneal dialysis independent of HDL-C, LDL-C and triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal dialysis treatment may further exacerbate lipoprotein abnormalities, and high levels of VLDL-C may lead the peripheral artery atherosclerosis [19, 20]. However, it is unclear whether VLDL-C level is an independent risk for mortality in PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Studies have consistently shown the ABI to have a minimum sensitivity and specificity of 90% and 98% respectively in predicting PAD, and with a minimum positive predictive value and negative predictive value of 90% and 98.63% respectively. [22][23][24][25][26][27][28][29] Despite the high burden of childhood NS, data on prevalence of PAD in children with NS is scarce. The study done in Egypt by Mohammed et al [4] among a cohort of children with NS recruited only those with steroid resistant NS, whereas the current study recruited all children with NS, irrespective of their steroid status.…”
Section: Introductionmentioning
confidence: 99%